Resilient Projection-based Distributed Leader-Follower Consensus Against Integrity Cyberattacks - Sadabadi, Mahdieh S. (Proceedings of the IEEE Conference on Decision & Control, 2024)
This paper focuses on the problem of distributed leader-follower consensus in multi-agent systems in which some agents are subject to adversarial attacks. We develop a resilient distributed leader-follower control strategy subject to integrity attacks, where agents' updates of their states can be compromised by injecting false signals to control inputs. Under such a threat model, we design a resilient distributed leader-follower framework for agents with continuous-time dynamics to resiliently track a reference state propagated by a leader. In the design of the resilient framework, projection-based operators are used as dynamic controllers to estimate the dynamics of uncertainties on the control inputs of each agent. By use of the properties of projection operators and Lyapunov stability theory, the uniform ultimate boundedness of the closed-loop multi-agent system in the presence of integrity attacks is guaranteed. The proposed resilient distributed scheme does not impose any limitations on the maximum tolerable number of cyberattacks and does not require high network connectivity. The effectiveness of the proposed resilient distributed consensus algorithm is verified by a numerical example.